Tren Harga Bawang Merah di Pasar Besar Kota Batu dan Pasar Sayur Karangploso Kabupaten Malang Periode Januari 2017 – Desember 2019 - Habib, Bahrul Muchlis; Sudibyo, Rahmad Pulung (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
Onions (Allium Cepa) is a vegetable that be a part of root vegetables such as carrot, potato, etc wich commonly used mainly the root part to be consumed. Onions known as one of the primary ingredient for food because it’s role as seasoning or as supplementary material like fried onions make it one of the ingredient with high economic value. Not surprisingly the price of onions commodity fluctuate everytime. Purpose of the research is : (1) knowing the onions price trend in Pasar Besar Kota Batu and Pasar Karangploso for the last 3 years (2) knowing the difference of the onions price trend between Pasar Besar Kota Batu and Pasar Karangploso. location determined intentionally (purposive). Data used for this research is secondary data obtained from Siskaperbapo or Sistem Informasi Ketersediaan dan Perkembangan Harga Bahan Pokok managed by Disperindag of East Java Province. Analysis used for this research is tabulation and chart, also least cost methode to show the trend happened also to project the possible price in the near future. The result show that the trend is tend to fluctuate annually but if we break down each month and use least cost method both location show a negatif price trend.